2010
DOI: 10.1016/j.jss.2010.03.062
|View full text |Cite
|
Sign up to set email alerts
|

HB-EGF Protects the Lungs after Intestinal Ischemia/Reperfusion Injury

Abstract: Background Acute respiratory distress syndrome continues to be a major source of morbidity and mortality in critically-ill patients. Heparin binding EGF-like growth factor (HB-EGF) is a biologically active protein that acts as an intestinal cytoprotective agent. We have previously demonstrated that HB-EGF protects the intestines from injury in several different animal models of intestinal injury. In the current study, we investigated the ability of HB-EGF to protect the lungs from remote organ injury after int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
(52 reference statements)
2
18
0
Order By: Relevance
“…Our findings implicated a critical role of TLR4 signaling in lung inflammatory injury triggered by intestinal I/R. Secondary lung inflammatory response plays a key role in the pathogenesis of acute lung injury in gut I/R [13][14][15], but the mechanisms of this process are poorly understood. Accumulation of neutrophils in the lung is a prominent feature of ALI after intestinal I/R [16].…”
Section: Discussionmentioning
confidence: 81%
“…Our findings implicated a critical role of TLR4 signaling in lung inflammatory injury triggered by intestinal I/R. Secondary lung inflammatory response plays a key role in the pathogenesis of acute lung injury in gut I/R [13][14][15], but the mechanisms of this process are poorly understood. Accumulation of neutrophils in the lung is a prominent feature of ALI after intestinal I/R [16].…”
Section: Discussionmentioning
confidence: 81%
“…Using the model of I/R, we investigated the ability of HB-EGF to protect the lungs from remote organ injury after intestinal I/R. We found that administration of HB-EGF led to decreased congestion of septae, reduced intra-alveolar inflammatory cell infiltration, decreased hemorrhage, and decreased cellular apoptosis in the lungs [93]. These results demonstrate that HB-EGF reduces the severity of acute lung injury after intestinal I/R in mice, and that HB-EGF may be a potential novel systemic anti-inflammatory agent for the prevention of distant organ associated with SIRS after intestinal injury.…”
Section: Effects Of Hb-egf During Intestinal Injurymentioning
confidence: 99%
“…1F). Because growth factor pathways have been implicated in various organs in response to IR injury (Casillas-Ramirez et al 2009, James et al 2010, Brzozowski et al 2012, we then evaluated the effect of IR on endogenous EGF and its receptor expression in testis. The plasma EGF remained relatively high along the study period but unexpectedly, no statistical difference was detected (Fig.…”
Section: Testicular Ir Stress Induces Endogenous Egf Expression In Micementioning
confidence: 99%